2019
DOI: 10.21273/hortsci14118-19
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Onion Bulb Endodormancy with Hydrogen Peroxide

Abstract: Long-day storage onion bulbs (Allium cepa) undergo a period of endodormancy that begins before harvest and lasts for several weeks, depending on the genotype. Onion seed production relies on cold treatment to break endodormancy and vernalize the bulbs. When bulbs are planted shortly after harvest, endodormancy results in delayed growth and, in turn, slower flowering and seed production. Through this work we sought to explore the use of hydrogen peroxide as a treatment to brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…Consistent with our observations concerning optimum vernalization time, we found that vernalization improves the uniformity of scape emergence and the proportion of plants that undergo floral initiation but is not a requirement for flowering [15]. Six weeks of vernalization resulted in uniform scape emergence in five of eight varieties, with over 66% of scapes emerging in under 120 days post-planting ( Figure 3B).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our observations concerning optimum vernalization time, we found that vernalization improves the uniformity of scape emergence and the proportion of plants that undergo floral initiation but is not a requirement for flowering [15]. Six weeks of vernalization resulted in uniform scape emergence in five of eight varieties, with over 66% of scapes emerging in under 120 days post-planting ( Figure 3B).…”
Section: Discussionsupporting
confidence: 91%
“…We previously determined that long day onion varieties can achieve uniform scape emergence with an optimum chilling time of 12 to 14 weeks at 10 °C [14]. Through the course of this work we identified and quantified an endodormancy period that is present in the bulbs of these varieties and lasts for 8 to 10 weeks [15]. This finding indicated that the bulbs were endodormant for more than half of the 14-week optimum chilling time.…”
Section: Introductionmentioning
confidence: 92%
“…Kendala utama budidaya bawang merah adalah adanya masa dormansi benih umbi selama 2 -4 bulan setelah tanam [3] yang dapat dikarenakan tingginya kandungan hormon asam absisat atau ABA [4]. Beberapa upaya untuk memecahkan dormansi umbi dapat dilakukan dengan suhu rendah, aplikasi gibberellin [5], pemotongan umbi [6], dan perendaman dengan hydrogen peroxide (H 2 O 2 ) [7]. Pemotongan umbi memiliki kelebihan dibandingkan dengan cara pemecahan dormansi lain yakni tidak membutuhkan alat dan bahan yang sulit dan dapat dilakukan dengan mudah.…”
Section: Pendahuluanunclassified
“…Hal ini sesuai dengan hasil penelitian dari [6] yang membuktikan bahwa pemotongan bibit umbi mampu meningkatkan parameter jumlah daun tanaman. Pemotongan umbi bibit bawang merah memberikan hasil lebih baik daripada umbi yang tidak dipotong pada seluruh komponen hasil yakni jumlah umbi (7,24), bobot basah umbi (21,56 g•tanaman -1 ) dan bobot kering umbi (17,30 g•tanaman -1 ). Pemotongan umbi bertujuan untuk mempercepat pertumbuhan [15] sehingga dapat meningkatkan komponen hasil.…”
Section: Metodeunclassified
“…Even though the total time from seed to seed is less than 24 months in a typical biennial breeding scheme, two growing seasons are generally required for this process. D'Angelo and Goldman [104] determined that uniform scape emergence in a greenhouse can be achieved in many long day onion genotypes with vernalization times of 12-14 weeks at 10 • C. They also examined the dormancy requirement for long-day onion and found that most long-day germplasm has an endodormancy period of 8-10 weeks [105]. They discovered that breaking dormancy and initiating root growth can be facilitated by a four-hour treatment of bulbs with 15% hydrogen peroxide [104].…”
Section: Bulb Dormancy and Vernalizationmentioning
confidence: 99%